2021
DOI: 10.1002/hfm.20901
|View full text |Cite
|
Sign up to set email alerts
|

User‐centered development of a worker guidance system for a flexible production line

Abstract: Worker guidance systems are digital assistance systems in production, which provide work‐related information and, thus, guide employees through production processes. This article describes the user‐centered development of such a worker guidance system for a flexible production line in a metrology company. Usage context analysis and requirements analysis illustrate the need for a simple and independent system that can be used voluntarily by employees. After two iterations of the human‐centered design process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Assembly work even becomes increasingly complex due to highly variable, individualized manufacturing processes (Egger-Lampl et al, 2019 ; Faccio et al, 2023 ). Various intelligent assistance systems (IAS) have been developed to effectively support assembly workers in their mostly monotonous but concentration-demanding jobs with the intention to reduce cognitive workload, and increase quality (Egger-Lampl et al, 2019 ; Kang et al, 2016 ; Stockinger et al, 2021 ). Although the (cognitive) support of assembly workers by such systems is intended (Berkers et al, 2022 ), the research field lacks specific theories and causal evidence on how IAS shape motivational work characteristics (MWC) (Baethge-Kinsky, 2020 ; Egger-Lampl et al, 2019 ).…”
mentioning
confidence: 99%
“…Assembly work even becomes increasingly complex due to highly variable, individualized manufacturing processes (Egger-Lampl et al, 2019 ; Faccio et al, 2023 ). Various intelligent assistance systems (IAS) have been developed to effectively support assembly workers in their mostly monotonous but concentration-demanding jobs with the intention to reduce cognitive workload, and increase quality (Egger-Lampl et al, 2019 ; Kang et al, 2016 ; Stockinger et al, 2021 ). Although the (cognitive) support of assembly workers by such systems is intended (Berkers et al, 2022 ), the research field lacks specific theories and causal evidence on how IAS shape motivational work characteristics (MWC) (Baethge-Kinsky, 2020 ; Egger-Lampl et al, 2019 ).…”
mentioning
confidence: 99%
“…Watson et al [59] and Jeske et al [60] explored the content design of information in WGSs and showed that it influences assembly performance, especially in training situations. Stockinger et al [30] also showed that especially the information level and information design affect the assembly performance. The importance of a good user experience of WGSs is regularly emphasized.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, the traditional production line is incapable to support data interaction, and can trace historical data in real time according to product production data, or deploy the technical problems and defects of work order execution information, product processing and quality information in the production line. [7][8][9] It is thus a pressing need to develop a method, system and platform for processing the product production data used for flexible production lines.…”
Section: Introductionmentioning
confidence: 99%